A rake's vow - Laurens, Stephanie; Copyright Paperback Collection (Library of Congress) (New York : Avon Books, 1998)
Accustomed to organizing her own affairs and those of her teenage brother, lovely Patience Debbington finds her life turned upside down by the dashing Vane Cynster, an arrogant rake with an antipathy toward matrimony.
Keywords: Cynster family (Fictitious characters) -- Fiction; Historical fiction; England -- Social life and customs -- 19th century -- Fiction; Love stories; Historical fiction; Regency fiction